Killing stalking. 4 - Koogi (Seven Seas Entertainment, 2023)
Min Jieun's body has been found, and it's all over the news. Officer Yang Seungbae immediately begins to hunt down every lead he can, disregarding the risks of that hunt at every turn. When Oh Sangwoo takes Yoon Bum to his part-time job, the officer makes a bold move. What will happen when he follows Yoon Bum into the bathroom to question him?